Dual Active Intermediates Induced LiOH Formation via the OH‐Rich Proton Donor in Li−O2 Batteries - Song, Li‐Na; Wang, Xiao‐Xue; Wang, Huan‐Feng; Wang, Yue; Wu, Jia‐Yi; Sun, Yu; Xu, Ji‐Jing (Advanced functional materials, 2025)
Generally, water displays a dominated impact on the solution growth mechanism of the aprotic lithium−oxygen (Li−O2) batteries, however, the high reaction activity and laborious secondary chemistry transformation process are associated with the irreversible utilization of water. In this paper, a substituted proton‐containing, highly dispersed and hydroxyl group (−OH)‐rich contained catalyst is employed in the Li−O2 battery chemistry, and lithium hydroxide (LiOH) is identified as the primary discharge product. Intriguingly, the hydrogen (H) in LiOH comes solely from the added −OH‐rich onion carbon (OLC), which is capable of building a high‐speed proton transfer bridge between the generated moieties of dual active intermediates superoxide species (O2−) and the moderate hydroperoxide (HO2−) over the platinum (Pt) active sites. The new mechanism involving the HO2− intermediate realizes a hydrogen transfer process via O2− nucleophilic attack toward OLC, which significantly suppresses the O2−‐related side reactions. Thereby, the batteries with Pt/OLC attain a high specific capacity of 12 500 mAh g−1 at a current density of 100 mA g−1, exceptional energy efficiency (100%), and remarkable rechargeability. In addition, the strong OLC‐DMSO interaction inhibits the lithium metal corrosion caused by the shuttle reactions and ensures favorable battery cycling stability. The promising results open up a new reaction pathway for Li−O2 battery electrochemistry. −OH‐rich onion carbon loaded with platinum cathode (Pt/OLC) is employed for Li−O2 batteries with LiOH as discharge product, in which Pt/OLC provides H for LiOH generation, OLC builds high‐speed proton transfer bridge between dual active mediators over Pt active sites. Based on this novel mechanism, O2−‐related side reactions are significantly suppressed, contributing to high specific capacity and remarkable rechargeability.